Integrated Pest Management Strategies for Fruitfly (Bactrocera cucurbitae) in Bittergourd (Bactrocera cucurbitae) - Tamilselvi , C.; Vijayashanthi , V.A.; Sathish, G.; Yogameenakshi, P.; Preethi , TL.; Sivagamy , K.; Banumathy, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present study was conducted to evaluate the effects of Integrated Pest Management practices against bitter gourd fruit fly in Tiruvallur District, Tamil Nadu, India. The demonstration was conducted at farmer’s fields in two village viz., Kilambakkam and Periya kilambakkam of the district Tiruvallur during Kharif season 2018 and 2019. The front line demonstration was consisted of IPM (Field sanitation, fruit fly baits, Installation of fruit fly traps and spraying of neem oil 3%) and Non –IPM practices (Spraying of chemical insecticides). When compared to non-IPM fields, IPM techniques with fruit fly traps (with cue lure) attracted a large number of fruit flies, resulting in a 64 percent reduction in fruitfly infestation and a 3-4 times higher yield. The use of pheromone traps instead of insecticides to control fruit flies results in significant cost savings and pesticide-free bitter gourd output.Results indicated average fruit yield of 12.80 t/ha, an increase of 55.29% increase in yield over farmers practice as well as a net income of Rs.1,62,700/-. Reduction in cost of cultivation due to less investment for plant protection aspects has been recorded